Consistent improvement in health-related quality of life with tiotropium in patients with chronic obstructive pulmonary disease: Novel and conventional responder analyses. (November 2016) - Tashkin, Donald P.; Bateman, Eric D.; Jones, Paul; Zubek, Valentina B.; Metzdorf, Norbert; Liu, Dacheng; Leonard, Thomas; Clerisme-Beaty, Emmanuelle; Wise, Robert A.
Abstract: Introduction: Improving health-related quality of life (HRQoL) in COPD patients is an important pharmacotherapeutic objective. This study investigated the extent, consistency, and durability of tiotropium maintenance therapy impact on HRQoL in moderate-to-very severe COPD. Methods: Patients received once-daily tiotropium 18 μg (n = 5244) or placebo (n = 4799) via HandiHaler ® (10 trials), or once-daily tiotropium 5 μg (n = 2622) or placebo (n = 2618) via Respimat ® inhaler (3 trials). St George's Respiratory Questionnaire (SGRQ) total scores were measured at baseline, and 6 months (13 trials) and 1 year (9 trials) from treatment start. Adjusted mean differences between treatments for change from baseline in total scores were calculated at each time-point for each trial. Responder and deteriorator rates (decrease or increase in score ≥4 units from baseline, respectively), net benefit (responder rate increase plus deteriorator rate decrease), and cumulative improvement and deterioration were determined. Results: Adjusted mean total score differences between treatments for change from baseline were significant (p < 0.05) in favor of tiotropium in 10/13 trials at 6 months and in 8/9 trials at 1 year. In all trials, estimated differences in responder rates between treatments favored tiotropium (significant [p < 0.05]: 5/13 trials at 6 months; 8/9 trials at 1 year). Net benefit favored tiotropium and cumulative improvement rates were consistently greater and deterioration rates consistently lower for tiotropium versus placebo. Conclusions: Tiotropium maintenance therapy significantly and consistently improved HRQoL in moderate-to-very severe COPD patients in a durable manner. These results may provide a benchmark for assessing benefits on HRQoL of other COPD treatments. Highlights: Novel SGRQ response analyses assessed HRQoL in COPD (tiotropium vs placebo). SGRQ total scores were consistently better for patients on tiotropium vs placebo. SGRQ score net benefit was better for tiotropium vs placebo at 6 months and 1 year. Tiotropium maintenance therapy vs placebo had long-term sustained benefit on HRQoL. These data may be a benchmark to assess benefits on HRQoL of other COPD therapies.